# 3(w-3)-3=-4(-6w+2)-7w

## Simple and best practice solution for 3(w-3)-3=-4(-6w+2)-7w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3(w-3)-3=-4(-6w+2)-7w equation:

3(w-3)-3=-4(-6w+2)-7w
We move all terms to the left:
3(w-3)-3-(-4(-6w+2)-7w)=0
We multiply parentheses
3w-(-4(-6w+2)-7w)-9-3=0

We calculate terms in parentheses: -(-4(-6w+2)-7w), so:
-4(-6w+2)-7w
We add all the numbers together, and all the variables
-7w-4(-6w+2)
We multiply parentheses
-7w+24w-8
We add all the numbers together, and all the variables
17w-8
Back to the equation:
-(17w-8)

We add all the numbers together, and all the variables
3w-(17w-8)-12=0
We get rid of parentheses
3w-17w+8-12=0
We add all the numbers together, and all the variables
-14w-4=0
We move all terms containing w to the left, all other terms to the right
-14w=4
w=4/-14
w=-2/7

`